Angle dependent conductivity in graphene FET transistors. (February 2015) - Fuentevilla, C.H.; Lejarreta, J.D.; Cobaleda, C.; Diez, E.
Highlights: A top gate voltage nonperpendicular to the source-drain in a pristine graphene FET has been proven to create an effective gap. Noticeable on–off ratios can be achieved by effectively tuning the FET parameters. Abstract: In this work we analyze a model of conductance across a field effect transistor built of monolayer graphene. We show how a top gate voltage non-perpendicular to the source-drain direction creates an effective gap in pristine graphene devices. We have studied several scenarios in order to model the presence of inhomogeneities in the graphene and its influence in the creation of an effective gap showing that it is a robust effect. Moreover, although the gap appears for any angle of the top-gate, tuning the FET parameters we achieve noticeable on–off ratios overcoming one of the main difficulties of graphene transistors.